After Rwanda
XX, 253 p.
Keywords: When the United Nations sanctions a humanitarian relief operation, how can the numerous and diverse UN, Non-Governmental Organizations and military elements be coordinated? What are the practical, political and institutional considerations and impediments? What can be learned from previous experience? This is a volume of practitioner perspectives: the views of distinguished individuals from all of the concerned professions, including former Special Representatives of the Secretary-General and Force Commanders, as well as senior UN officials and representatives of the NGO community.